Application of Workflow in Multi-Agent System Organization - Neri, José R. F.; Hübner, Jomi F.; Santos, Carlos H. F. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper presents a proposal for a model to integrate a workflow system into a multi-agent organizational model. Three alternatives are evaluated and the best alternative is integrated into the Moise organizational framework. An example of the chosen model is shown and a comparison based on workflow patterns is presented. The advantages of using this model are also discussed.